THE ROLE OF ESP IN INTERNATIONAL BUSINESS AND NEGOTIATIONS THE CONTRIBUTION OF PRIVATE UNIVERSITIES - Shahrabonu Qurbonova; Maftuna Nurova (TADQIQOTLAR, 2025)
Annotation:  This article discusses the changing role of internet shopping in modern  consumer  trends  and  business  practice.    It  analyzes  the  advantages  and disadvantages of e-commerce, its effect on traditional retailing, and the technology developments behind this shift.  The article provides solutions to problems and tips for safe and effective online shopping